Developing Online Modules for Educators in Fifth Grade Physical Education Class - Yudesta Erfayliana; Nevzat Demirci; Pervin Toptaş Demirci (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The purpose of this research is to develop online modules for educators in fifth-grade physical education classes. The participants of this study totaled 12 people who were divided at the validation and product trial stages. The design of this research is research & development. Research instruments are observation sheets, interview sheets, questionnaire sheets, and documentation sheets. Data analysis techniques are quantitative and descriptive. The results of the research and conclusions are (1) The online module is declared valid by media, materials, and language experts, and (2) the online module is declared suitable for use by educators and learners. The contribution to the next research is in the manufacture of online module teaching materials for educators in physical education (PJOK) class V subjects there are some obstacles or difficulties that may be an improvement for other researchers to develop online module teaching materials. for educators in PJOK class V subjects with other materials. Keywords: physical education, module, online, elementary school